Heating boiler operator's manual : maintenance, operation, and repair - Malek, Mohammad A. (McGraw-Hill's AccessEngineering., 2007)
Offers guidelines for the operation, maintenance, and repair of heating boilers. This title is useful as a guide for the Heating Boiler Exam and to increase your understanding of boiler principles.